[Heimaey Harbor] - Streng, Evelyn Fiedler (1975)
Photograph of Heimaey Harbor. Black, lava rock mountains surround a grey harbor lined by stone platforms in the background. Two ships, one white and black and the other green and white, sit along a dark platform along the right edge of the photograph. A white railing curves along the bottom left corner of the photograph. The sky is covered in grey clouds. Icelandic text sits along the edges of the ships.